2006
DOI: 10.1021/jp065966x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Toluene Adsorption on Na-Form Zeolite with a Temperature-Programmed Desorption Method

Abstract: Temperature-programmed desorption (TPD) of toluene was carried out on various zeolites, and theoretically analyzed to determine thermodynamic parameters. The TPD process was identified as the case of equilibrium control, showing that the analytical method, the same as that for ammonia TPD, can be applied to the toluene TPD to calculate the adsorption heat. It was observed that approximately one toluene molecule was adsorbed on one Na + cation for MFI and BEA. The heat of toluene adsorption on Na + was MOR > MF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 44 publications
4
27
0
Order By: Relevance
“…6. HBeta showed a dominant and symmetric peak at lower temperature (with maxima at 141°C), similar to the result in [26]. In contrast, two significant differences in the desorption profile of HBeta/Cd were observed: (i) the desorption stage at lower temperature is asymmetric; (ii) the desorption stage at higher temperature is evident.…”
Section: Analysis With Gcsupporting
confidence: 77%
See 1 more Smart Citation
“…6. HBeta showed a dominant and symmetric peak at lower temperature (with maxima at 141°C), similar to the result in [26]. In contrast, two significant differences in the desorption profile of HBeta/Cd were observed: (i) the desorption stage at lower temperature is asymmetric; (ii) the desorption stage at higher temperature is evident.…”
Section: Analysis With Gcsupporting
confidence: 77%
“…No significant mass number peak was observed except the mass numbers exclusive to toluene (39, 45, 46, 50, 51, 61, 62, 63, 65, 89, 91, 92, and 93). This suggested that toluene was reversibly adsorbed and desorbed on the bulk sample without considerable side reaction [26]. On the other hand, the MS signal of 91 over HBeta/Cd (see Fig.…”
Section: Analysis With Msmentioning
confidence: 96%
“…In the present work, it has been found that about 12% and 6% of o-xylene, on bentonite and silica, respectively, remained adsorbed although the isothermal desorption curve reached zero. This adsorptive behavior suggests the use of the Temperature-Programmed Desorption (TPD) method for determination of desorption energy Ed value, as firstly reported by Cvetanovic, then by several authors [1,9,[40][41][42]. The method is based on measuring the desorption profile with temperature increase, which goes through a maximum and finally back to zero, indicating that the surface is cleared of adsorbate.…”
Section: Application Of the Isosteric Heat Methodsmentioning
confidence: 81%
“…Therefore, acidity is quite important to trap and hold HCs until high temperatures are reached under our experimental conditions. Niwa's group has recently reported that Na + plays a quite interesting role in holding HC due to the electrostatic interaction with aromatic pi electrons [19]. High silica zeolites are applied in such an adsorbent owing to their hydrophobic interaction and micropore filling.…”
Section: Resultsmentioning
confidence: 99%